An experimental class to illustrate the physical and chemical effects of ultrasound as an introduction to practical advanced oxidation processes - Efraím A. Serna-Galvis; Ricardo A. Torres-Palma (Ultrasonics Sonochemistry)
This work presents the development of an illustrative experimental class about the mechanical and chemical effects of ultrasound to introduce students to the field of sonochemical advanced oxidation processes. Ultrasound equipment at low frequency (<100 kHz) and mid-high frequency (200–500 kHz), in addition to basic laboratory equipment (glassware instruments and a spectrophotometer) and accessible reagents (commercial activated carbon, potassium iodide, ammonium heptamolybdate, distilled water, and methyl orange) are required. Under the teacher’s supervision, the students will perform experiments on the sonication of activated carbon in water to learn about the mechanical effects. Meanwhile, to evidence the chemical effects, the water sonolysis to produce hydrogen peroxide, and the degradation of a model organic pollutant (methyl orange) are carried out. In qualitative aspects, the students will learn the predominant effects as a function of the ultrasound frequency. From a practical point of view, the students are expected to learn how to quantify the sonogenerated hydrogen peroxide and follow the sonochemical degradation of a model compound. Besides, a short-written report and its feedback are presented as the evaluation strategy for the learning of students.